The role of preserved bowel and mesentery fixation in apple-peel intestinal atresia - Jinbao Han; Zenghui Hao; Long Wang; Ting Yao; Wei Fan; Zheng Zhao; Liuming Huang; Zhilin Xu (BMC, 2022)
Abstract Objective This study explored the feasibility of mesoplasty with end-to-side anastomosis in the treatment of different apple-peel mesenteric defects with high jejunal atresia. Methods A retrospective analysis was performed on 42 premature infants admitted to the hospital between 2014 and 2021. Prenatal ultrasound scans revealed bowel dilatation. The patients experienced vomiting after birth and produced white or no meconium. Plain radiography showed double or triple bubble signs and the patients underwent emergency laparotomy. High jejunal atresia with different apple-peel atresia appearance was discovered intraoperatively, involving mobilization of the ileocecal region. Patients received end-to-side anastomosis between the enlarged blind pouch and atretic bowel, as well as mesoplasty. A jejunal feeding tube was placed trans-nasally. Patients were discharged after achieving full enteral feeding. We also reviewed the literature on the subject. Results Three patients died and 39 survived. The discharged patients were followed up for 12 months, and none showed post-operative complications such as intestinal obstruction, malnutrition, or chronic diarrhea. All surviving patients reached the expected height and weight for children of the same age. Conclusion For cases of high jejunal atresia with apple-peel intestinal atresia, mesoplasty may be a good option to avoid postoperative volvulus.